Evaluation of genetic differences between two autochthonous Spanish cattle breeds - Paola E. Milia; Alberto Cesarani; Clara Diaz; Cristina Meneses; Juan Carlos Parejo; Laura Falchi; Nicolò P. P. Macciotta; Corrado Dimauro (Italian Journal of Animal Science)
Genetic diversity was assessed in five subpopulations (Negra-MORB and Cárdena-MORC for Morucha breed; Jarda-JAR, Bociblanca-BOC, and Avileña-Negra Ibérica breed-ANI for Avileña Negra Ibérica main breed) belonging to two local Spanish cattle breeds (Avileña Negra Ibérica-AVI and Morucha-MOR) by using univariate and multivariate statistical approaches. A total of 4,137 animals (2,785 ANI, 333 BOC, 127 JAR, 263 MORB and 629 MORC) were genotyped with the Affymetrix Beadchip Microarray HD. After quality control, 30,391 common SNPs were retained. In the univariate approach, the Wright fixation index (FST) was computed between and within breeds. In the multivariate approach, the stepwise discriminant analysis and the canonical discriminant analysis (CDA) were applied. The highest weighted FST value (0.05) was computed between BOC and MORB. Instead, the lowest values were found between ANI and JAR and between ANI and BOC. In the multivariate approach, CDA significantly discriminated the five breeds by using 1,144 markers. Of the four Canonical functions (CAN1, CAN2, CAN3 and CAN4) extracted by CDA, CAN1 fully separated AVI and MOR whereas CAN2 disentangled the two subpopulations of MOR. Considering CAN3 and CAN4, the CDA separated AVI subpopulations. Among markers selected by both FST and CDA, the top 10 discriminant SNPs were mapped to genomic regions harbouring genes involved in coat colour, behaviour, and morphological traits. This study confirmed that the two breeds, different at phenotypic level, are different also at genetic level. Moreover, the results showed that MOR subpopulations are more different from each other than the AVI ones.